Glial Glutamate Transporters Maintain One-to-One Relationship at the Climbing Fiber–Purkinje Cell Synapse by Preventing Glutamate Spillover - Takayasu, Yukihiro (J Neurosci, 2006)
A glial glutamate transporter, GLAST, is expressed abundantly in Bergmann glia and plays a major role in glutamate uptake at the excitatory synapses in cerebellar Purkinje cells (PCs). It has been reported that a higher percentage of PCs in GLAST-deficient mice are multiply innervated by climbing fibers (CFs) than in the wild-type (WT) mice, and that CF-mediated EPSCs with small amplitude and slow rise time, designated as atypical slow CF-EPSCs, are observed in these mice. To clarify the mechanism(s) underlying the generation of these atypical CF-EPSCs, we used (2S,3S)-3-[3-(4-methoxybenzoylamino)benzyloxy]aspartate (PMB-TBOA), an inhibitor of glial glutamate transporters. After the application of PMB-TBOA, slow-rising CF-EPSCs were newly detected in WT mice, and their rise and decay kinetics were different from those of conventional fast-rising CF-EPSCs but similar to those of atypical CF-EPSCs in GLAST-deficient mice. Furthermore, both slow-rising CF-EPSCs in the presence of PMB-TBOA in WT mice and atypical CF-EPSCs in GLAST-deficient mice showed much greater paired-pulse depression compared with fast-rising CF-EPSCs. In addition, both of them were more markedly inhibited by γ-d-glutamyl-glycine, a low-affinity competitive antagonist of AMPA receptors. These results indicated that both of these types of EPSCs were mediated by a low concentration of glutamate released from neighboring CFs. Based on all of these findings, we suggest that glial transporters prevent glutamate released from a single CF from spilling over to neighboring PCs other than the synaptically connected PC, and play an essential role in the maintenance of the functional one-to-one relationship between CFs and PCs.